Insights into the diachrony of the East Baltic subjunctive mood - Fries, Simon; Hill, Eugen (Baltistica, 2022)
This article intends to shed light on the diachrony of the subjunctive mood (also labelled optative or conditional) in the two East Baltic languages Latvian and Lithuanian. It is demonstrated to what extent the subjunctive paradigms in both languages – especially Old Lithuanian, Old Latvian and modern Lithuanian dialects – reflect original source constructions based on infinitival verb-formations, namely the supine (e. g. Lith dúo-tų, Latv duô-tu, cf. Old Prussian dā-tun, OCS da-tŭ) and the infinitive (e. g. Lith dúo-ti, Latv duô-t, cf. OPr dā-t, OCS da-ti). The systematic comparison of Baltic and Slavic evidence indicates that most forms of the Lithuanian and Latvian subjunctive paradigms go back to two Proto-East-Baltic source constructions that both contained the supine of a respective verb and forms of the copula (Lith bū́ti, Latv bût): (a) the supine joined with present tense forms of the copula, and (b) the supine joined with past tense forms of the copula. One remarkable exception is a heteroclitic 1sg. form in Lithuanian that is shown to share a common source construction with the Latvian debitive. The remainder of the article is dedicated to the emergence of secondary subjunctive forms in modern Lithuanian dialects (especially Aukštaitian dialects in the South and East of Lithuania). It is discussed to what extent these forms reflect the interplay of regular diachronic processes, namely (proportional) analogy and sound change. The findings presented in the discussion have interesting implications for the common morphological and phonological prehistory of both East Baltic languages.